2013
DOI: 10.4161/cc.25785
|View full text |Cite
|
Sign up to set email alerts
|

Pirh2

Abstract: PerSPeCtive U biquitylation is currently recognized as a major posttranslational modification that regulates diverse cellular processes. Pirh2 is a ubiquitin E3 ligase that regulates the turnover and functionality of several proteins involved in cell proliferation and differentiation, cell cycle checkpoints, and cell death. Here we review the role of Pirh2 as a regulator of the DNA damage response through the ubiquitylation of p53, Chk2, p73, and PolH. By ubiquitylating these proteins, Pirh2 regulates cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Furthermore, recent work identified the PIRH2 E3 ligase as a regulator of CHK2 stability and showed that USP28 can interact with PIRH2 and CHK2 in the context of USP28 overexpression (61). Interestingly, PIRH2 was also implicated in regulating c-Myc stability and the DDR (61)(62)(63). While again consistent with previous data suggesting that USP28 regulates CHK2, the functional relevance of this interaction for the DDR remains unclear, as we have found that Usp28 knockout animals do not recapitulate any of the predicted phenotypes, such as destabilized CHK2 or impaired IR-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent work identified the PIRH2 E3 ligase as a regulator of CHK2 stability and showed that USP28 can interact with PIRH2 and CHK2 in the context of USP28 overexpression (61). Interestingly, PIRH2 was also implicated in regulating c-Myc stability and the DDR (61)(62)(63). While again consistent with previous data suggesting that USP28 regulates CHK2, the functional relevance of this interaction for the DDR remains unclear, as we have found that Usp28 knockout animals do not recapitulate any of the predicted phenotypes, such as destabilized CHK2 or impaired IR-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pirh2, an E3 ligase that promotes the degradation of p53 (see above) can also target p63 and p73 for proteasomal degradation [235]. Pirh2 is able to ubiquitinate TAp63 and ∆Np63, which have been found to be vital for normal cell differentiation in the context of keratinocytes [218].…”
Section: Pirh2mentioning
confidence: 99%
“…Pirh2 (p53-induced protein with an RING-H2 domain) [96] is a RING-containing E-3 ligase able to bind to and target all members of the p53 family for degradation [97,98,99,100]. Pirh2 is able to induce degradation of both TAp63 and ΔNp63 isoforms [99], in cooperation with the E-2 enzyme UbcH5b [97].…”
Section: The Ubiquitin-proteasome System and P63 Regulationmentioning
confidence: 99%
“…Pirh2 can also induce degradation of p73 [99,101], and p21 [86]. It can be transactivated by p53, another example of a negative feedback loop and possible competition between family members [96]. …”
Section: The Ubiquitin-proteasome System and P63 Regulationmentioning
confidence: 99%